Uji Kemampuan Adsorpsi Komposit Keratin Bulu Itik-Polietilena Terhadap Ion Besi(III) - Oktavia Hesti Fauzy; Uripto Trisno Santoso; Umi Baroroh Lili Utami (Universitas Lambung Mangkurat, 2022)
Research on the adsorption of iron(III) ion using an adsorbent from duck feather-polyethylene composite has been studied. This study aimed to determine the optimum pH conditions and the optimum contact time required in the iron(III) ion adsorption process. Optimum pH and contact time are then measured using AAS to determine the amount of iron(III) ion adsorbed with the duck feather-polyethylene composite adsorbent. The determination of the optimum pH was carried out with pH variations which are 2, 3, 4, 5, 6, 7, and 8, while determination of the optimum contact time was carried out with contact time variations which are 40, 60, 80, 100, 120, 140, and 160 minutes. The result of this research showed that optimum conditions for iron(III) ion adsorption at pH 6 and contact time at 80 minutes, which each adsorption capacity are 68.33% and 79.78%.